COVID‐19 as an accelerator for digitalization at a German university: Establishing hybrid campuses in times of crisis - Skulmowski, Alexander; Rey, Günter Daniel (Human behavior and emerging technologies, 2020)
As a result of the COVID‐19 outbreak, teaching in universities needed to be quickly transitioned from regular on‐campus classes into technology‐enhanced teaching formats. In this article, we present the case study of Chemnitz University of Technology (Germany), where digital classes were introduced in a matter of weeks. By analyzing syllabus data, we found that the use of video and video conferencing is an important current development. Related to these findings, we present evidence from instructional psychology and social media research that can help in the design of teaching during this crisis. We highlight the need for multimodal learning, that is, learning settings that use multiple sensory modalities. Importantly, we present a strategy of hybrid campuses for this and potential future emergencies. This approach describes how the social distancing measures currently in effect can be used to re‐think higher education based on a reasonable use of technology. Taken together, the COVID‐19 crisis can be a time of major reform in higher education that will accelerate the process of digitalization in an unprecedented way.